2012
DOI: 10.1111/j.1365-2486.2012.02757.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of nitrogen deposition and climate on carbon isotope discrimination and intrinsic water‐use efficiency of angiosperm and conifer trees under rising CO2 conditions

Abstract: The objective of this study is to globally assess the effects of atmospheric nitrogen deposition and climate, associated with rising levels of atmospheric CO2 , on the variability of carbon isotope discrimination (Δ(13) C), and intrinsic water-use efficiency (iWUE) of angiosperm and conifer tree species. Eighty-nine long-term isotope tree-ring chronologies, representing 23 conifer and 13 angiosperm species for 53 sites worldwide, were extracted from the literature, and used to obtain long-term time series of Δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
63
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 103 publications
14
63
0
1
Order By: Relevance
“…Tree growth rate might not increase proportionally with increase in photosynthesis because of other limiting factors such as nutrient availability [30,31]. Although experiment enrichment or short -term CO2 increase can lead to higher net primary productivity [32], tree ring analysis in the Mediterranean shows the opposite [33] probably due to limitations in water and nutrients availability [34,35]. This is in line, with the recorded tree growth reduction [36], increased growth variability [37] and defoliation in Mediterranean forests the last decades.…”
Section: Land Use Changessupporting
confidence: 65%
“…Tree growth rate might not increase proportionally with increase in photosynthesis because of other limiting factors such as nutrient availability [30,31]. Although experiment enrichment or short -term CO2 increase can lead to higher net primary productivity [32], tree ring analysis in the Mediterranean shows the opposite [33] probably due to limitations in water and nutrients availability [34,35]. This is in line, with the recorded tree growth reduction [36], increased growth variability [37] and defoliation in Mediterranean forests the last decades.…”
Section: Land Use Changessupporting
confidence: 65%
“…The European δ 13 C tree-ring records analyzed by Frank et al (2015) and Saurer et al (2014) also point to a moderate control towards a constant c i /c a ratio. Leonardi et al (2012) conclude that the temporal variation in δ 13 C in their long-term isotope tree-ring chronologies for 53 sites worldwide supports the hypothesis of an active plant mechanism that maintains a constant ratio between intercellular and ambient CO 2 concentrations. Lévesque et al (2014) reported, from their δ 13 C tree-ring data, an increase in iWUE over the last 50 years in the range of 8 to 29 % for xeric and mesic sites in the Alps and Switzerland.…”
Section: Consistency With Previous Studiesmentioning
confidence: 65%
“…These data generally suggest small to moderate decadal-to-century-scale changes in discrimination that correspond to a 20th century increase in iWUE On the order of 20 % and physiological control towards a constant ratio of the partial pressure of CO 2 within the leaf's substomatal cavities to the CO 2 pressure outside the leaf (c i /c a ; Saurer et al, 2004;Leonardi et al, 2012;Frank et al, 2015) and, more generally, a pattern of stomatal optimization towards minimizing water loss per unit carbon assimilated (Voelker et al, 2016). The δ 13 C data are used to evaluate global and local models of plant growth, carbon cycling, and land-atmosphere isotopic fluxes for atmospheric carbon balancing (Scholze et al, 2003(Scholze et al, , 2008Suits et al, 2005;Danis et al, 2012;van der Velde et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…同 化 的 碳 量 ) 定 量 表 达 (Singh & Gupta, 1977;Baldocchi, 1994) (Leonardi et al, 2012;Battipaglia et al, 2013;Grossiord et al, 2014)。Zhou等(2014 …”
Section: 碳同化和水分蒸腾由植物通过气孔行为控制 通常用水分利用效率(Wue 即单位水分消耗量所unclassified